The Influence of Customer Interface Quality (CIQ) on Consumer Satisfaction and its Impact on Consumer Loyalty - Fathorrahman Fathorrahman; Ummi Wahyuni; Zainurrafiqi Zainurrafiqi; Nurul Hidayati (Pusat Riset dan Inovasi Nasional, 2024)
In today's increasingly competitive retail environment, Customer Interface Quality (CIQ) plays a vital role in shaping consumer satisfaction and fostering loyalty. This study focuses on the retail setting of Basmalah Store in Pamekasan Regency, aiming to investigate the influence of CIQ on consumer satisfaction and its subsequent impact on consumer loyalty. The research addresses the problem of how digital and physical interface elements affect consumer perceptions and behavior in retail service encounters. The objective is to identify whether enhancing CIQ can significantly improve customer satisfaction and lead to stronger loyalty. A quantitative research design was employed using a survey method, targeting a sample of 100 consumers selected through purposive sampling. Data were collected from individuals who had shopping experiences at Basmalah Store during a defined period. The analysis reveals that CIQ has a significant positive effect on consumer satisfaction, which in turn significantly contributes to consumer loyalty. The synthesis of findings suggests that improving customer interface elements—such as ease of use, responsiveness, and visual appeal—can foster higher levels of satisfaction, encouraging consumers to remain loyal to the brand. This study concludes that retail businesses should strategically invest in optimizing customer interface features to strengthen customer relationships and sustain long-term business performance.